Application of open multi-commodity market data model on the communication bandwidth market - Przemysław Kacprzak; Mariusz Kaleta; Piotr Pałka; Kami Smolira; Eugeniusz Toczyłowski; Tomasz Traczyk (Journal of Telecommunications and Information Technology, 2023)
In the paper the market model for balancing communication bandwidth trade (BCBT) is analyzed in the form of multi-commodity market data model (M3). The distinguishing feature of BCBT model is that it assumes that market players can place buy offers not only for isolated network resources – inter-node links, but also for end-to-end network paths of predefined capacity, that is, every offer concerns a point-to-point bandwidth connection between a pair of specified locations in a communication network. The model enables effective balancing of sell and buy offers for network resources in a way which maximizes global economic welfare. The open multi-commodity market data model provides efficient and clear mechanisms, which support the environment of auctions and multi-commodity exchanges, especially when the trade is constrained by the infrastructure resources. Thus the model may be used in designing open information systems for market balancing and clearing in the context of multicommodity trade in various network infrastructure sectors.